Planning for Implementation Science in Clinical Practice Research: An Augmentative and Alternative Communication Example. - Binger, Cathy; Douglas, Natalie; Kent-Walsh, Jennifer (American Journal of Speech-Language Pathology, 2022)
Purpose: Most evidence-based clinical research findings in communication sciences and disorders never achieve full implementation by practicing clinicians. To address this almost universal problem, this tutorial focuses on the initial planning steps of including implementation methodologies as part of clinical practice research programs. Integrating the principles and methodologies of implementation science can shift the current reality, leading to better uptake of evidence-based interventions. Method: A step-by-step approach to integrating implementation science into new or existing research projects is provided, including the construction of a logic model, the selection of an implementation framework, and the selection of research methodologies. A detailed example of an augmentative and alternative communication research program is provided to illustrate the process. Conclusions: Readily available online tools can help researchers start the process of integrating implementation science into clinical practice research, and existing frameworks can assist with developing and guiding research programs to ensure maximal impact. If the ultimate goal is to improve the daily lives of individuals with communication disorders through the use of evidence-based practices, clinical practice researchers must integrate these approaches into their research programs.